Outcome of appendicectomy in children performed in paediatric surgery units compared with general surgery units. Issue 6 (2nd April 2014) - Tiboni, S; Bhangu, A; Hall, N J; Panagiotopoulou, I G; Chatzizacharias, N; Rana, M; Rollins, K; Ejtehadi, F; Jha, B; Tan, Y-W; Fanous, N; Markides, G; et al.
Abstract: Background: Appendicectomy for acute appendicitis in children may be performed in specialist centres by paediatric surgeons or in general surgery units. Service provision and outcome of appendicectomy in children may differ between such units. Methods: This multicentre observational study included all children (aged less than 16 years) who had an appendicectomy at either a paediatric surgery unit or general surgery unit. The primary outcome was normal appendicectomy rate (NAR). Secondary outcomes included 30-day adverse events, use of ultrasound imaging and laparoscopy, and consultant involvement in procedures. Results: Appendicectomies performed in 19 paediatric surgery units (242 children) and 54 general surgery units (461 children) were included. Children treated in paediatric surgery units were younger and more likely to have a preoperative ultrasound examination, a laparoscopic procedure, a consultant present at the procedure, and histologically advanced appendicitis than children treated in general surgery units. The unadjusted NAR was significantly lower in paediatric surgery units (odds ratio (OR) 0·37, 95 per cent confidence interval 0·23 to 0·59; P < 0·001), and the difference persisted after adjusting for age, sex and use of preoperative ultrasound imaging (OR 0·34, 0·21 to 0·57; P < 0·001). Female sex and preoperative ultrasonography, but not age, were significantly associated with normal appendicectomy in general surgery units but not in paediatric surgery units in this adjusted model. The unadjusted 30-day adverse event rate was higher in paediatric surgery units than in general surgery units (OR 1·90, 1·18 to 3·06; P = 0·011). When adjusted for case mix and consultant presence at surgery, no statistically significant relationship between centre type and 30-day adverse event rate existed (OR 1·59, 0·93 to 2·73; P = 0·091). Conclusion: The NAR in general surgery units was over twice that in paediatric surgery units. Despite a more severe case mix, paediatric surgery units had a similar 30-day adverse event rate to general surgery units. Service provision differs between paediatric and general surgery units. Abstract : Outcomes differ between centres